A multiparametric approach for rejuvenation of the Gaurikund geothermal spring system in the Northwest Himalayan region - KHANNA, Anurag; BAGCHI, Debasish; KANNAUJIYA, Suresh; SARKAR, Tandrila (Contributions to Geophysics and Geodesy, 2022)
The Gaurikund town falls on the way of the famous trekking route to Kedarnath that faced the wrath of the 2013 flood disaster. This fateful event severed more than 5000 casualties, demolished several infrastructures, and shifted the course of Gaurikund spring from its original position. Nevertheless, the Gaurikund geothermal spring system located in the Himalayan Geothermal Belt of the Garhwal region is preeminent for religious beliefs, balneotherapeutic values and a gateway to delve within the geothermal and hydrological characteristics of the area. In this perspective, restoration of Gaurikund geothermal spring system becomes a necessity. A multiparametric approach comprising geospatial, geology, hydrochemistry and geophysics has been used to study and justify these aspects at Gaurikund. The geological studies infer that the geothermal spring gets recharged by the steep, southerly dipping joints in granite gneiss. Subsequently, the deep percolated water heats up due to the high geothermal gradient and then emerge along the Vaikrita Thrust and its sympathetic minor fault-thrust system by advection. Moreover, four spring outlets are inventoried, with discharge varying from 7.46 to 95.54 L/min. The normal emissivity model uses the pre and post-disaster satellite data and generates maximum kinetic temperature images, showing a positive correlation between land surface temperature and spring discharge. Two-dimensional Electrical Resistivity Tomography (Schlumberger, Wenner and Gradient configurations) survey revealed two low resistivity zones proximal to the geothermal spring on the right bank of the Mandakini river. The engineering interventions carried out by bank protection and construction of small gully plugs in the catchment area is recommended along Gaurikund-Sonprayag section on the right bank of Mandakini river.